The Comparison of Drawing Family and the House-Tree-Person Test in Children with Addicted and Non-Addicted Parents - Marjan Shafiei; Hosein Salimi; Ezat ollah Kordmirza (Drug Control Headquarters, Research and Education Office, 2013)
Objective: This study is aimed at comparing results of the draw-a-family test and the house-tree-person test in the children with addicted and non-addicted parents. Method: This is a scientific-comparative study in which 50 children with addicted parents attending Tehran rehab centers and 50 children with non-addicted parents who were selected using the random cluster sampling method were measured by means of the draw-a-family test and the house-tree-person test. Findings: Results suggest that drawing indices in the are more in the house-tree-Person paintings and family drawings of the children with addicted parents in comparison to the non-addicted group, scoring higher in terms of the number of drawing indices such as depression and anxiety symptoms, weak self-esteem, and valuelessness. Conclusion: It can be said that the parents' drug abuse intensifies and expedites children's physical, affective and behavioral problems.